(untitled) (Research, Society and Development, 2022)
The waste of water resources and the increase in water consumption in urban systems, has generated major problems of water scarcity. The vehicle washing process is a major consumer of water and also generates an enormous volume of potentially polluting effluents, being released directly or with inadequate treatments to the sewage and / or pluvial network. This article aimed to develop a concept for an equipment for the treatment of effluents by electrolysis of a vehicle washing station capable of reducing the environmental impact of this activity through the treatment and reuse of the effluent. To elaborate the concept, the product development methodology of the authors Pahl et al. Was used, specifically the planning and conception phases, where the project requirements and the concept for the equipment for the treatment of effluents by electrolysis were established. The designed equipment consisted of an electrolytic chamber with a foam scraper followed by a decanter, in addition to the other operational controls. Feeding and unloading was carried out by centrifugal pumps.